Study of Approaches to Designing Public Buildings for People with Limited Mobility (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Designing public buildings that cater to the needs of individuals with limited mobility is a critical issue that transcends mere architectural considerations, encompassing principles of inclusivity and accessibility. As urban environments evolve, the urgency for effective design strategies intensifies, particularly in identifying and addressing the impediments faced by these populations.